Freedom of expression and right to honor in judicial reasoning. Analysis based on a case study - Alarcón Requejo, Gílmer (2020)
Through the comparative analysis of the judgments issued in the framework of the complaints filed against the journalist Pedro Salinas, this article allows us to appreciate the judicial criteria used in the resolution of the fundamental conflict between the right to honor and the right to freedom of expression and information. The units of analysis are the first instance sentences where the referred journalist appears as prosecuted for the crime of aggravated defamation. Given the factual particularities that characterize the case study, these units make it possible to appreciate important changes in the conceptual dimensions and in the legal criteria emanating from the sources of law. The analysis accepts, in part, the methodological proposal prepared by Atienza to evaluate the arguments of the sentences both formally, materially and pragmatically, within the framework of a Democratic rule of law.